Dampak Reverse Logistics Terhadap Agri-Food Supply Chain - Ismawati, Ismawati; Rahma, Lailatul; Muflikh, Yanti Nuraeni; Suprehatin, Suprehatin (Universitas Galuh, 2025)
Increasing awareness of environmental issues, sustainable development, and the benefits of recycling underscores the significance of incorporating reverse logistics into supply chain systems. The primary objective of this study is to pinpoint the obstacles and repercussions associated with the integration of reverse logistics on the performance of supply chains by means of a methodical examination of existing literature. Employing a systematic literature review, this study scrutinized research patterns related to reverse logistics within supply chains. A total of 27 articles, spanning from 2014 to 2023, were meticulously chosen via a procedure involving identification, screening, eligibility evaluation, and analysis, with data derived from reputable sources such as Google Scholar, Scopus, and ScienceDirect. The analysis brought to light that impediments like financial constraints, inadequate understanding of reverse logistics methodologies, and absence of governmental regulations pose as major hindrances to the adoption of reverse logistics. Nonetheless, the implementation of reverse logistics has been validated to yield favorable outcomes on supply chain performance by enhancing system efficiency, cutting down expenses, boosting customer contentment, and advocating sustainable business strategies. To facilitate the execution of reverse logistics, governments ought to formulate unambiguous regulations, while enterprises can explore financial backing from investors or engage in partnerships with other stakeholders in the supply chain to secure essential funds.